Effect of Sutural Pattern on Shell Shape: A Case Study Including Two Ammonite Subfamilies from the Western India - Roy, Pinaki (The Nucleus, 2023)
Shell morphology of ammonites and its connotation with ecological constraints has long been a matter of debate. The present study involves comparison of shell morphology with sutural complexity between Eucycloceratin and Reineckein ammonites of Kutch and Jaisalmer from India. Statistically significant differences between fractal-dimensions (Df), whorl expansion rate of evolute and involute shells are interpreted. There is also a correlation between the flank’s shape and complexity of suture. The planulate shells show highest Df value and the lowest ones are found in whorl cross section with convex flanks. It may also be stated that sutural complexity is not the primary function to resist shell implosion and is thereby related to bathymetry.